Awareness and Use of Serials in an African University Library: Faculty and Students’ Perspective - Nutsupkui, Erica; Owusu-Ansah, Christopher M. (Information Management and Business Review, 2017)
The purpose of this study was to examine the use of print serials by students and faculty members of a satellite campus of the University of Education, Winneba. Specifically, this study sought to determine the level of awareness and use of serials among faculty and graduate students, and how this affect their perception of the value of print serials in teaching and learning. The study made use of survey research methods through the use of questionnaires. The population of the study consisted of 165 faculty members and 97 graduate students, with an eventual return rate of 66% each, respectively. The findings of the study revealed that both faculty and graduate students were, relatively, aware of the print serial collection in the library. However, despite this awareness, they used print serials, relatively, less frequently. Again, the study established that both faculty and students have significant positive perceptions on the usefulness of print serials in their teaching, learning and research roles. We recommend to librarians to create awareness of print serial collections while updating the collection, and enhance the positive perception of print serials by demonstrating, through outcome measures, how the use of print serials can be beneficial to the academic and research community.